Ultra-rapid auxin metabolite profiling for high-throughput mutant screening in Arabidopsis - Pencík, Aleš; Casanova-Sáez, Rubén; Pilarová, Veronika; Žukauskaite, Asta; Pinto, Rui; Micol, José Luis; Ljung, Karin; Novák, Ondrej (Journal of Experimental Botany, 2018)
Auxin (indole-3-acetic acid, IAA) plays fundamental roles as a signalling molecule during numerous plant growth and development processes. The formation of local auxin gradients and auxin maxima/minima, which is very important for these processes, is regulated by auxin metabolism (biosynthesis, degradation, and conjugation) as well as transport. When studying auxin metabolism pathways it is crucial to combine data obtained from genetic investigations with the identification and quantification of individual metabolites. Thus, to facilitate efforts to elucidate auxin metabolism and its roles in plants, we have developed a high-throughput method for simultaneously quantifying IAA and its key metabolites in minute samples (<10 mg FW) of Arabidopsis thaliana tissues by in-tip micro solid-phase extraction and fast LC-tandem MS. As a proof of concept, we applied the method to a collection of Arabidopsis mutant lines and identified lines with altered IAA metabolite profiles using multivariate data analysis. Finally, we explored the correlation between IAA metabolite profiles and IAA-related phenotypes. The developed rapid analysis of large numbers of samples (>100 samples d-1) is a valuable tool to screen for novel regulators of auxin metabolism and homeostasis among large collections of genotypes.
Keywords: mutace; extrakce na pevné fázi; rostlinné proteiny; High-Throughput Nucleotide Sequencing; Multivariate Analysis; Plant Proteins; Solid Phase Extraction; Arabidopsis; Indoleacetic Acids; tandemová hmotnostní spektrometrie; Chromatography, Liquid; multivariační analýza; kyseliny indoloctové; Mutation; chromatografie kapalinová; vysoce účinné nukleotidové sekvenování; Tandem Mass Spectrometry